2017
DOI: 10.1080/00380768.2017.1282300
|View full text |Cite
|
Sign up to set email alerts
|

Lack of yield response in potato (Solanum tuberosum L.) to phosphate fertilizer under contrasting soil types varying in phosphate absorption coefficient and available phosphate

Abstract: There is growing evidence of excessive use of phosphate fertilizer and high residual soil phosphate levels in arable cropping systems in Japan. However, there is a lack of regional-scale information on the current status of soil-available phosphate as well as its impacts on a potato (Solanum tuberosum L.) cropping system. Although phosphorus is an essential nutrient, there have been confounding reports about the effects of excessive soil-available phosphate on potato tuber yields. This study was conducted in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[ 25 ] The soils in Tokachi are derived from various volcanic ashes characterized by a relatively high phosphorus binding ability causing a relatively low phosphorus availability for plants. [ 21 ] However, if the soil is the sole determining factor, the phosphorus content in one location should be consistently either lower or higher than that in the other location regardless of the year of cultivation. The phosphorylation reaction of amylopectin is catalyzed by the α‐glucan water dikinase enzyme, of which substrates include water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 25 ] The soils in Tokachi are derived from various volcanic ashes characterized by a relatively high phosphorus binding ability causing a relatively low phosphorus availability for plants. [ 21 ] However, if the soil is the sole determining factor, the phosphorus content in one location should be consistently either lower or higher than that in the other location regardless of the year of cultivation. The phosphorylation reaction of amylopectin is catalyzed by the α‐glucan water dikinase enzyme, of which substrates include water.…”
Section: Resultsmentioning
confidence: 99%
“…[20] In the meantime, the tuber yield showed no response to phosphate fertilization rates in the studies conducted in 170 potato grower fields in Hokkaido, Japan, indicating that reducing the phosphate fertilization rate within certain limits may have no negative impact on the tuber yield. [21] Compared to the effect of mineral nutrients such as phosphorus on crop yield, their impact on starch quality has hardly been understood. [22] In the case of cassava starch, it was reported that an increase in the phosphate fertilization rate during tuber cultivation resulted in an increased phosphorus content in the starch in association with significant changes in various physicochemical properties of the starch.…”
Section: Location Of Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus fertilisers commonly used in agriculture are usually in the form of plant-absorbable phosphates, which are derived from phosphate rock deposits and converted through a series of physical and chemical processes so that they can be effectively absorbed by the plant's root system. However, the overapplication of phosphorus fertiliser can encourage overexuberant plant respiration, resulting in greater dry matter consumption than accumulation, which can lead to premature maturity and lower yields [9]. Potassium (K), one of the important nutrients that regulate various physiological and biochemical processes in plants [10], increases photosynthesis and biomass when applied, but it also increases transpiration in trees and may exacerbate water stress in plants, resulting in problems such as increased water stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to that in open-field farming, an intense application of phosphate fertilizer in a covered greenhouse environment results in an increased accumulation of surplus phosphorusbearing compounds (surplus-P) in the soil (Fan et al, 2020;Wang et al, 2015). Although crop yield is not affected by additional phosphate fertilization of phosphate-accumulated soils (Gondwe et al, 2017), farmers often hesitate to reduce phosphate fertilizer application. To establish adequate soil management recommendations, it is important to elucidate the chemical forms of surplus-P that determine mobility and plant availability of surplus-P. Phosphate in soil is mainly sorbed on aluminum (Al) and iron (Fe) oxide minerals, aluminosilicate clays and calcium carbonate or precipitated with Al, Fe, or calcium (Ca) (Gerard, 2016).…”
Section: Introductionmentioning
confidence: 99%